Is bullying and suicide a problem for East Asia's schools? Evidence from TIMSS and PISA. Issue 2 (3rd March 2020) - Rappleye, Jeremy; Komatsu, Hikaru
ABSTRACT: Herein we examine the dominant image of East Asian schools as marked by a darker side of widespread bullying, leading to high rates of youth suicide. First outlining the substantial literature on bullying in the English language, we turn to show how – paradoxically – the rates of bullying and suicide are no higher, or in nearly all cases, lower than both Anglo-American systems (Australia, England, New Zealand, United States) and high PISA performers (Canada, Finland, Estonia). To explain this, we extend a constructivist approach proposed by sociologists of Japanese youth, suggesting that recurrent 'moral panics' such as bullying are determined, at least in part, by underlying differences in self-construal and views of how society functions. This analysis contributes to recent work that has challenged persistent stereotypes of East Asian education, those images blocking deeper engagement with the underlying differences in approach and philosophy these systems represent.